Pembelajaran Efektif Membaca Al-Qurâan Dengan Metode Iqra` Di Raudhatul Athfal - Subur, Mastiti (PROGRAM STUDI PENDIDIKAN GURU RAUDLATUL ATHFAL (PGRA) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2016)
This paper explores how learning to read Al-Qur`an for children effectively according to the standard reading level of children. In practice, the teacher always makes lesson planning and preparing the necessary tools that are fitted to the subject matter of Al-Qur`an according module Iqra` one method, as well as paper cards achievement. Effectiveness in the classical method changes with depth evaluation into individual methods for better results. With the method of classical children who did not master can not be known while using each individual child can be controlled progress. In addition, its effectiveness is supported by knowledge of the obstacles in learning to read the Quran that is; lack of support from parents, the child does not follow Al-Qur`an learning in the community, child who always wants to play, as well as the reason for the book Iqra` methods are not taken or hyperactive children.